2018
DOI: 10.1021/jacs.8b08510
|View full text |Cite
|
Sign up to set email alerts
|

Sodorifen Biosynthesis in the Rhizobacterium Serratia plymuthica Involves Methylation and Cyclization of MEP-Derived Farnesyl Pyrophosphate by a SAM-Dependent C-Methyltransferase

Abstract: The rhizobacterium Serratia plymuthica 4Rx13 releases a unique polymethylated hydrocarbon (CH) with a bicyclo[3.2.1]octadiene skeleton called sodorifen. Sodorifen production depends on a gene cluster carrying a C-methyltransferase and a terpene cyclase along with two enzymes of the 2- C-methyl-d-erythritol 4-phosphate (MEP) pathway of isoprenoid biosynthesis. Comparative analysis of wild-type and mutant volatile organic compound profiles revealed a C-methyltransferase-dependent C alcohol called pre-sodorifen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 39 publications
(107 reference statements)
0
61
0
6
Order By: Relevance
“…The most prominent bacterial terpenes are geosmin and methyl isoborneol (summarized in Dickschat, 2016). Recently a sesquiterpene with a unique structure was isolated from Serratia plymuthica (von Reuss et al, 2010(von Reuss et al, , 2018. Terpene synthases are fascinating enzymes as they are quite limited regarding their substrate usage (GPP, FPP, GGPP, NPP, and/or respective enantiomers), however their reaction mechanisms (including several cyclization cascades) can release a multitude of products (multi product enzymes).…”
Section: Biosynthesis Of Mvocsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent bacterial terpenes are geosmin and methyl isoborneol (summarized in Dickschat, 2016). Recently a sesquiterpene with a unique structure was isolated from Serratia plymuthica (von Reuss et al, 2010(von Reuss et al, , 2018. Terpene synthases are fascinating enzymes as they are quite limited regarding their substrate usage (GPP, FPP, GGPP, NPP, and/or respective enantiomers), however their reaction mechanisms (including several cyclization cascades) can release a multitude of products (multi product enzymes).…”
Section: Biosynthesis Of Mvocsmentioning
confidence: 99%
“…Terpene synthases are fascinating enzymes as they are quite limited regarding their substrate usage (GPP, FPP, GGPP, NPP, and/or respective enantiomers), however their reaction mechanisms (including several cyclization cascades) can release a multitude of products (multi product enzymes). It is interesting to note, that the elucidation of the sodorifen biosynthesis led to a change of paradigm, as the substrate for the sodorifen terpene synthase is a methylated and cyclic FPP, produced by an upstream acting SAM-dependent C-methyltransferase (von Reuss et al, 2018).…”
Section: Biosynthesis Of Mvocsmentioning
confidence: 99%
“…Many of the TCs identified in these studies appear to be transcriptionally silent but their expression in an engineered Streptomyces heterologous host has enabled the identification of a number of unprecedented terpene NPs 108 , and novel TC families will surely continue to be discovered regularly. Indeed, it was recently shown that the organic volatile sodorifen (20) produced by S. plymuthica 4Rx13 is the product of a TC 109,110 , a remarkable finding given that every C atom in the bicyclic ring structure of the compound is substituted with either a methyl or methylene group, which previously obscured the biosynthetic origins of this molecule 111 . Unusual methylations of C5 building blocks have also been reported for the biosynthesis of a number of other structurally unique bacterial terpenes, with longestin 112 (21) and the teleocidins 113 (22) representing additional characterized examples.…”
Section: Terpenesmentioning
confidence: 99%
“…A similar mechanism may also be relevant for the biosynthesis of sodorifen, [28] a polymethylated homosesquiterpene in which one additional Me group equivalent is introduced by an SAM-dependent methylation, but in this case, three more Me groups seem to originate from internal methylene groups of FPP. [29] Despite preliminary results from labelling experiments that have resulted in a biosynthetic hypothesis, [29] a detailed mechanistic investigation for the biosynthesis of this molecule is lacking. In the case of the homomonoterpene 2-methylisoborneol, one additional Me group is introduced by SAM-dependent methylation of GPP, but the subsequent terpene cyclisation of the resulting 2methyl-GPP is regular.…”
Section: Communicationsmentioning
confidence: 99%